Monetary Stability Regulation In The Perspective Of Islam And Interest Rate Model - Safitri, Rifninda Dwi; Soebagyo, Daryono (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Cirebon, 2024)
A monetary policy solely reliant on Taylor Rules may not be capable of addressing the holistic economic challenges involving social norms and Islamic principles. This research challenges the conventional reliance on Taylor Rules in monetary policy by proposing an alternative approach rooted in Islamic principles and social norms. Traditional monetary policy primarily focuses on managing inflation through interest rate adjustments, as per Taylor's rule. However, this study explores the feasibility of an Islamic framework that emphasizes discouraging excessive consumption, unproductive investment, and speculation, alongside inflation control. Employing qualitative research methods and drawing on existing literature, this study suggests that adopting such an approach could offer benefits, particularly in a country like Indonesia. By prioritizing ethical considerations and social norms, Indonesia could promote responsible economic behavior among individuals and businesses. This holistic approach moves beyond relying solely on interest rates to combat inflation and can foster a balanced and sustainable economic environment. Overall, the study highlights the advantages of integrating Islamic principles and social norms into monetary policy, enhancing its effectiveness, resilience, and potential for long-term stability and sustainable economic growth.